Economic costs and returns from organic farming in Oyo state, Nigeria (2015)
The study evaluated the costs and returns of organic farming using the farmers in Akinyele Local Government of Oyo state, Nigeria as case study. An interview schedule was administered to the respondents to elicit useful information. The analysis was based on input and output data collected from one hundred and eighty farmers selected at random from the area from which eighty-eight used organic farming, fifty-eight used non-organic farming and thirty-four used both farming systems. The data were analysed using descriptive statistics, Duncan Multiple Range Test (DMRT), t-test group statistics and gross margin analysis. Results of the analysis indicated that 57.8% of the respondents were male, 66.1% were married and all the respondents had formal education either at primary, secondary or tertiary level. Furthermore, 48.9% of the respondents adopted organic farming system, 32.2% adopted non-organic farming system while 18.9% adopted both organic and non-organic farming systems. From the gross margin analysis done, both organic and non-organic farming are profitable. However, it is more profitable to produce vegetable and maize organically. Costs related to fertiliser and the post-harvest preservation and sales was higher in non-organic farming, whereas the cost of crude farm implements and labour was higher in organic farming. There should be an intensified awareness to improve the level of participation of farmers in organic farming, recommendation of organic products to people, and government policies that encourage farmers to go into organic farming, especially by making their products readily disposable in already prepared market at encouraging prices.